Moving organizational atmospheres - Lydia L. Jørgensen (Copenhagen Business School (CBS), 2019)
Moving Organizational Atmospheres provides a conceptual and empirical exploration of the notion of organizational atmosphere as a non-dualist concept. The atmospheric is presented as an organizational phenomenon with relevance for decision makers, organizations and managers as it concerns aesthetic, affective-emotional and spatial qualities of the work environment, but also addresses issues of profound cultural transformation and social change. As such, organizational atmospheres are considered part of an ongoing aesthetization of society that pervades the emotionalaffective climate of organizations and everyday human actions to respond to desires, creativity and the quest for constant growth. Looking at organizational atmosphere from a non-dualist perspective, shows organization as an aesthetic phenomenon manifesting itself in and stimulating the emotional-affective climate, the practices, the spaces and the ways of working in organizations. Both conceptually and analytically the thesis contributes to the discussions in the fields of organizational aesthetics as well as the affective and spatial turn in organization studies, by addressing how organizational atmospheres work when embraced as a fluid phenomenon and by providing an analytically experimental account of the experiencing and producing organizational atmosphere based on field work in two organizations. Considering organizational atmosphere as a non-dualist notion, implies embracing ambiguity by attending to subject and object as forming a coherent whole in human experience. The thesis presents a systematic and in-depth engagement with a 'German' non-dualist tradition of thinking the atmospheric in organization studies by tracing the philosophical roots in the German phenomenological tradition, spearheaded by the neo-phenomenology of Hermann Schmitz and Gernot Böhme's aesthetics. Coherently, dealing empirically with organizational atmosphere raises a set of pivotal ontological and epistemological questions, which leads to arguing for a performative research approach to engage with organizational atmosphere as a relational ontological matter coming into momentary presence in the lived space through the embodied affective experience. As such the thesis reflects a move towards understanding organization as an atmospheric phenomena reflecting an aesthetic and processual apprehension, whereby not only considering organizations as part of an aesthetization of society, but proposing a rethinking of organizational categories and the ways of writing organization.
hdl:10398/9750
Keywords: 650; Betriebsklima; Bibliometrie; Wirtschaftsphilosophie; Deutsch